(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
This paper shed light on the relationship between economic growth and unemployment in Iraq by using Okun’s law to determine the potential output. Our results indicate to a decline in Okun’s coefficient which consistent with weak job recovery. And the increasing growth rate does not sufficient condition for decreasing unemployment rate in Iraq. The results also show that Iraqi economy still unproductive with idle production capacity and not diversified.Furthermore, the structure of labor market is inflexible and dominated by government and one sector represented by oil sector which is not intensive-labor.